2022
DOI: 10.3389/fpubh.2022.828542
|View full text |Cite
|
Sign up to set email alerts
|

When Does Da Vanci Robotic Surgical Systems Come Into Play?

Abstract: The emergent of medical science and technology has risen the minimally invasive surgery. Da Vinci Robotic Surgical Systems (RSS) is the trend at present. Compared with the past surgical methods, many studies related to RSS tend to explore postoperative outcomes and quality of life or compare the advantages and disadvantages than the other surgery. Few studies to understand the patients' willing who use RSS. This study mainly explores the patients' willingness and adopts the Technology Acceptance Model (TAM) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Although accumulated evidence has shown the significant impact of perceived ease of use on both perceived usefulness and usage intention [ 15 - 17 ], in this study, perceived ease of use turned out to be trivial in the context of CAs. Not coincidentally, some studies on information system usage in hospitals have also shown the insignificant relationship between perceived ease of use and usage intention [ 36 - 38 ]. This result indicates that once CAs prove to be useful and effective, patients will consider it worth their time and effort to learn how to use CAs.…”
Section: Discussionmentioning
confidence: 99%
“…Although accumulated evidence has shown the significant impact of perceived ease of use on both perceived usefulness and usage intention [ 15 - 17 ], in this study, perceived ease of use turned out to be trivial in the context of CAs. Not coincidentally, some studies on information system usage in hospitals have also shown the insignificant relationship between perceived ease of use and usage intention [ 36 - 38 ]. This result indicates that once CAs prove to be useful and effective, patients will consider it worth their time and effort to learn how to use CAs.…”
Section: Discussionmentioning
confidence: 99%
“…As robotics have evolved over the last 25 years, the scientific evidence has continued to accumulate in response to the rapid adoption of this technology by surgeons across specialties. Today, there are more than 30,000 peer-reviewed publications on da Vinci robotic-assisted surgery 2 . However, as robotics have been integrated into each specialty, safety, feasibility, and reproducibility have been concerns for surgeons and hospitals.…”
mentioning
confidence: 99%
“…Today, there are more than 30,000 peer-reviewed publications on da Vinci robotic-assisted sur-gery. 2 However, as robotics have been integrated into each specialty, safety, feasibility, and reproducibility have been concerns for surgeons and hospitals.…”
mentioning
confidence: 99%